Efficient Assessment of Risk of Fall. Issue 6 (6th April 2016) - Forrest, George; Chen, Eric
Abstract: Purpose: The aim of this study was to identify factors that are associated with risk of falls on rehabilitation unit and to determine an efficient and inexpensive method of identifying patients at high risk for fall. Design: Retrospective record review. Method: Retrospective review of 2, 254 consecutive admissions to an inpatient rehabilitation unit. Findings: Score on the Functional Independence Measure (FIM) at the time of admission and length of stay are the factors that most highly correlate with risk of fall. Use of the mobility and problem solving or transfer and problem solving scales can identify patients at high risk for fall. Conclusion: Low scores on total FIM, and the mobility and problem solving items indicate increased risk of fall. Clinical Relevance: Nurses need to take appropriate measures to protect the safety of these patients.